Application of Panoramic T2 Sequence for Magnetic Resonance Imaging of Lumbosacral spine: Aplicación de Secuencia T2 Panorámica para Resonancia Magnética de Columna lumbosacra - Román Meza, Alexander Humberto (2021)
Introduction: The evaluation of the total spine by magnetic resonance imaging in a T2-weighted single sequence using Software Composing previous planning, called panoramic, would be beneficial in the study of lumbosacral spine for the additional information that could be obtained. Objective: To analyze the application of T2 panoramic sequence for magnetic resonance imaging of the lumbosacral segment. Methods: Retrospective and cross-sectional study executed with 186 cases selected by stratified probability sampling, between 18 and 60 years old, using a form consisted of a general sheet and an analytical sheet obtained from the request for radiological study and the examination itself. Results: Of the total, 80.1% were in the adult stage of life, and 53.8% were female, and 52.7% had the suspicion of herniated disc as a specific diagnostic presumption. Degenerative pathologies were mainly presented, with 93%, having herniated discs as the most frequent with 57%, which included extruded, protruded and migrated hernias with 40.6%, 37.9% and 21.5 % respectively. Likewise, it was verified with hypothesis test that this acquisition allows to localize 50% more findings in contrast to the usual examination, defining that this sequence should be applied because it localizes findings in a greater number in comparison to the lumbosacral selective examination. Conclusions: In general, it was defined that the application of this panoramic T2 sequence is more usefulness for a better evaluation, because it achieves greater findings, resulting as main pathologies in lumbosacral, cervical and dorsal segments those of a degenerative type, standing out the herniated discs.